Language Attitudes of the Madurese Community Toward Madurese, Indonesian, English, and Other Foreign Languages - Misnadin Misnadin; Susi Yuliawati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
Language attitudes play an important role in the use and maintenance of a language. This is particularly the case in a multilingual speech community such as the Madurese community where most people speak more than one language. The present study seeks to understand the attitudes of the Madurese community toward Madurese, Indonesian, English, and other foreign languages (MIEof languages). To achieve this, 200 questionnaires were randomly distributed to respondents in Bangkalan, Sampang, Pamekasan, and Sumenep, but only 150 questionnaires were filled in and returned. The questionnaires, which contained questions and answers using 5 point Likert scales of ‘strongly agree, agree, neutral, disagree, and strongly disagree’, were analyzed quantitatively by averaging the calculation results of each of the scales. The results were categorized based on relevant themes, i.e., attitudes toward learning, mastery, and use of MIEof languages. Our analyses showed that most of the respondents demonstrated positive attitudes toward learning, mastery, and use of MIEof languages. The results are discussed with respect to the language maintenance of Madurese and local languages, the prospects of Indonesian, English, and other foreign languages along with multilingualism practices in Madura. It can be concluded that the Madurese community seem to be open to the practice of multilingualism, indicated by their positive attitudes toward language learning, mastery, and use. It is suggested that future studies make use of qualitative data, such as interview data so that findings about the language attitudes of the Madurese community under consideration can be further corroborated.